The Aztecs : A Very Short Introduction - Carrasco, David (Oxford, New York Oxford University Press, 2012)
This Very Short Introduction employs the disciplines of history, religious studies, and anthropology as it illuminates the complexities of Aztec life. Readers meet a people highly skilled in sculpture, astronomy, city planning, poetry, and philosophy, who were also profoundly committed to cosmic regeneration through the thrust of the ceremonial knife and through warfare. David Carrasco looks beyond Spanish accounts that have colored much of the Western narrative to let Aztec voices speak about their origin stories, the cosmic significance of their capital city, their methods of child rearing.
Include Index and Illustration
Keywords: Aztecs